2020
DOI: 10.1016/j.annonc.2020.08.1775
|View full text |Cite
|
Sign up to set email alerts
|

1711P SARS-CoV-2 infection in prostate cancer patients: Data from a high-incidence area in Italy

Abstract: Background: Novel SARS-CoV-2 infection has been a severe health problem in Italy since the beginning of March 2020, with around 227,000 confirmed cases on May 18th, 2020. The north-western part of Tuscany has been one of the areas with the highest incidence (342/100,000 inhabitants) and the highest lethality rate (31,2/ 100,000 inhabitants). The lethality rate was higher in men than women (12.6% vs. 7.4%). People aged 70-79 represented half of this population and the deaths in this subgroup represented 15.9% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A search of the PubMed and Scopus databases and the proceedings of ASCO, ESMO, AUA, and EAU meetings from 1 January 2020 to 1 September 2021 identified 14 studies reporting the outcomes of PC patients with SARS-CoV-2 infection: five were published in the form of full papers (Caffo et al, 2020a;Di Lorenzo et al, 2020;Jimenez-Alcaide et al, 2021;Klein et al, 2021;Montopoli et al, 2020), and the others as letters (5) (Caffo et al, 2020b;Dalla Volta et al, 2020;Koskinen et al, 2020;Kwon et al, 2021;Patel et al, 2020) or meeting abstracts (4) (Duarte et al, 2021;Patel et al, 2021;Sbrana et al, 2020;Tucker et al, 2021). The results are summarised in Table 1.…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Pc Patients Rec...mentioning
confidence: 99%
See 2 more Smart Citations
“…A search of the PubMed and Scopus databases and the proceedings of ASCO, ESMO, AUA, and EAU meetings from 1 January 2020 to 1 September 2021 identified 14 studies reporting the outcomes of PC patients with SARS-CoV-2 infection: five were published in the form of full papers (Caffo et al, 2020a;Di Lorenzo et al, 2020;Jimenez-Alcaide et al, 2021;Klein et al, 2021;Montopoli et al, 2020), and the others as letters (5) (Caffo et al, 2020b;Dalla Volta et al, 2020;Koskinen et al, 2020;Kwon et al, 2021;Patel et al, 2020) or meeting abstracts (4) (Duarte et al, 2021;Patel et al, 2021;Sbrana et al, 2020;Tucker et al, 2021). The results are summarised in Table 1.…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Pc Patients Rec...mentioning
confidence: 99%
“…The severity of infection outcomes in ADT + patients was usually expressed in terms of mortality, which ranged from 5.3%-38.2% (Caffo et al, 2020a, b;Dalla Volta et al, 2020;Jimenez-Alcaide et al, 2021;Klein et al, 2021;Kwon et al, 2021;Tucker et al, 2021). Two studies reported a mortality rate of 0%, but they respectively evaluated only one and two ADT + patients with infection (Di Lorenzo et al, 2020;Sbrana et al, 2020). Two studies investigated infection severity in terms of mortality and intensive care unit (ICU) admissions and, in these cases, severe outcomes were recorded in respectively 16.6 % and 25 % of patients (Koskinen et al, 2020;Montopoli et al, 2020).…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Pc Patients Rec...mentioning
confidence: 99%
See 1 more Smart Citation